THE COMMUNICATIVE APPROACH IN ESL TEACHING - Комар, Ольга (Modern engineering and innovative technologies, 2024)
In today's society, rapid integration changes and social tensions are affecting various aspects of life. This also applies to education, which requires changes in curricula and the development of various competences of teachers. One of the most important